Who wants Safer Streets? Explaining Concern for Public Safety in Brazil - Menno Pradhan; Martin Ravallion (Tinbergen Institute, 2001)
Public action to prevent crime is often driven by concerns about public safety. But what generatesthose concerns ? ]s it crime, or something else ? Using survey data for Brazil, we find that thedesire for greater public safety has a positive own-income effect, but a negative neighborhood-income effect; living in a poor area increases concern for public safety at given own-income. Theown-income effect is nonlinear, such that inequality attenuates the aggregate concern for greatersafety. Education raises concern, and strongly so when neighbors are poorly educated. Controllingfor these factors, we identify a significant causal effect of lack of public safety on the desire forgreater safety.
Keywords: D12; D60; H41; 330; Perceived public safety; crime; inequality; Brazil; Öffentliche Sicherheit; Nachfrage; Soziale Schicht; Wohnstandort; Brasilien